Avaliação de sincronização lateral entre pedestre e passarela utilizando um excitador pneumático controlado por lógica fuzzy - Andrade, Alexandre Ribeiro (2011)
In large span footbridges, it has been observed that pedestrian traffic can induce low frequency oscillations. The proximity between the natural frequencies of the structure and the frequencies of the excitation can result in the occurrence of resonance phenomenon, causing difficulties to use the structure for fear of its collapse on the part of users. Notably, the increased amplitude of the vibration, in the lateral direction that have been induced by crowds of pedestrians were brought to attention by the behavior of some footbridges that presented excessive vibration in this direction such as the Millennium Bridge in London, Solferino Bridge in Paris, among others. The lateral movement can cause alteration on the movement of the center of gravity of the pedestrian during the crossing and thus discomfort to transit on it. On the other hand, the lateral movement of the structure can induce synchronization between pedestrians and the structure s own move, resulting in amplification of vibrations, a phenomenon identified in the literature by lock-in. However, research on the relationship between frequency and amplitude of motion of the structure and percentage of synchronization that this motion induces on the pedestrians are incipient, which hampers the development of mathematical models to analyze the phenomenon. To investigate this phenomenon, we developed a control system using fuzzy logic to control a pneumatic system excitation applied in a prototype footbridge built in the laboratory. The system was conceived to provide oscillatory movement, with control of frequency and amplitude. Results showed that pedestrians tend to synchronize with the footbridge, causing the lock-in effect in the lateral direction, when the footbridge lateral oscillation approaches by half of the pedestrian pacing rate in vertical direction.